An Assessment on Maritime Students' Awareness, Perceptions and Needs in Career Planning in Tertiary Education - Özdemir, Pınar (Transactions on Maritime Science, 2024)
Although seafaring is seen as an attractive profession for prospective students in terms of having the opportunity to see different parts of the world while working and earning more money in less time compared to other professions, the harsh conditions of duties onboard sometimes overshadow this attractiveness, which may lead students to question their choices and seek different career alternatives. This study aims at assessing maritime students' knowledge, perceptions, and needs regarding career awareness and career planning at the tertiary level. The study also seeks to understand students' awareness of career-related activities and the role and responsibilities of the career centre. The research component of the study involves administering a questionnaire to 381 first-year students at a maritime-focused university. The questionnaire comprises twenty questions based on a five-point Likert scale and has been electronically distributed. The data collected has been analysed using parametric methods based on four variables: career anchor, career awareness, career centre awareness, and career planning awareness. The study has revealed that most of the students are aware of their own characteristics and the sacrifices required by their future profession, but they had not yet decided which career path to follow after graduation. The study has also revealed that students are interested in developing their skills through extracurricular activities and consider entrepreneurship as a future career option. The results suggest that career offices in maritime universities should create more opportunities to provide students with adequate information about their future careers and to enable them to make correct and realistic decisions about their career paths. The next study on this topic can focus on how to raise awareness of the functions of career officers and how to develop maritime-oriented career planning courses so that the students can make more realistic and satisfying career choices.